A Search for QPOs in the Blazar OJ287: Preliminary Results from the 2015/2016 Observing Campaign - Zola S.; Valtonen M.; Bhatta G.; Goyal A.; Debski B.; Baran A.; Krzesinski J.; Siwak M.; Ciprini S.; Gopakumar A.; Jermak H.; Nilsson K.; et al. (M D P I AG, 2022)
We analyse the light curve in the R band of the blazar OJ287, gathered during the 2015/2016 observing season. We did a search for quasi-periodic oscillations (QPOs) using several methods over a wide range of timescales. No statistically significant periods were found in the high-frequency domain both in the ground-based data and in Kepler observations. In the longer-period domain, the Lomb–Scargle periodogram revealed several peaks above the 99% significance level. The longest one—about 95 days—corresponds to the innermost stable circular orbit (ISCO) period of the more massive black hole. The 43-day period could be an alias, or it can be attributed to accretion in the form of a two-armed spiral wave.